An application of Palmer's drougth index to a semi-arid tropical region - Suárez, María E. (1987)
Palmer's Drought Index (PDI) was applied to a semi-arid region in Costa Rica. In the computations of the water balance, two modificaions to Palmer´s method were made. Th e method of Hargreaves was used to obtain potential evapotranspiration and the procedure of Thornwaite and Mather to obtain potential runoff. The period analysis in the region was from june 1972 to december 1983 (i.e. 138 months), of which 32% had drought conditions, with 7% mild, 11% moderate, 11% severe, and 3% extreme droughts (according to Palmer´s classification). The values obtained for the PDI were tested against reports from the press concerning crop damage by droughts and very good agreement was found. The dependence of the PDI on the available water capacity of the soil and the potential evapotranspiration is also discussed.